MODEL SIMULASI PENGELOLAAN AIR PADA EMBUNG KECIL MANULAI II - Pentewati, Priseila; Seran, Sri Santi Leoporda Maria Fatima; Takeleb, Aderita Mariana; Taa, Peregrinus Dhae Siga (Eternitas: Jurnal Teknik Sipil, 2024)
Embung Kecil Manulai II is one of the air storage infrastructures that plays an important role in supporting air needs in the community area of Kupang Regency, East Nusa Tenggara Province. This study aims to turn on the reservoir's storage capacity, analyze the potential to provide air needs, and identify gaps in its management. The methods used include hydrological data collection, analysis of the mainstay discharge, and simulation of storage capacity using hydrological software. The results of the study indicate that Embung Kecil Manulai II is able to accommodate air up to a certain maximum capacity to meet irrigation and domestic needs, especially during the rainy season. However, during the dry season, water availability tends to decrease significantly, so more optimal management is needed, including the use of rainwater harvesting technology and strengthening community participation. The simulation model developed provides an overview of the reservoir's performance projections in various climate scenarios and future air needs. This study is expected to be the basis for planning effective and sustainable water resource management in the region.